Evaluation of the Nutritive Value of Sorghum Variety ICSV400 in Broiler Diets - Jamaa , N.A.; Abubakar, M.M.; Oyawoye, E.O. (International Journal of Poultry Science, 2014)
An experiment was conducted to evaluate the nutritive value of sorghum variety ICSV400 as a replacement for maize in broiler diets. Five diets were formulated for both the starter and finisher phases, in which the sorghum variety ICSV400 was included at 0, 25, 50, 75 and 100% replacement levels and the diets designated as treatments T1, T2, T3, T4 and T5, respectively. Sorghum variety ICSV400 was used to replace maize as a dietary energy source. Two hundred day old Anak 2000 broiler chicks were allotted to the five treatments in a completely randomized design. Each of the five treatments was replicated four times, with ten birds per replicate. At the starter phase, birds on T1 consumed significantly (p<0.01) less feed (61.63 g) than birds on T5 (74.35 g), T2 (73.98 g) and T4 (71.85 g), similar to those on T3 (67.07 g). Daily weight gain (24.02-33.04 g) and feed conversion ratio (2.26-2.83) were not significantly affected by dietary treatments. The finisher and pooled phases no significant differences between treatments were observed for all the parameters analyzed. Carcass parameters were not affected by dietary treatments but small intestine weight tended to decrease with increasing level of sorghum. Feed cost in N/kg gain tended to be lower (N166.90) in diet 4 (75% sorghum) and higher (N 213.58) in diet 3 (50% sorghum). It was concluded therefore that sorghum variety ICSV400 can completely replace maize in broiler diets without adverse effects on the general performance of the birds.